The application of PAX1 methylation detection and HPV E6/E7 mRNA detection in cervical cancer screening. Issue 8 (25th May 2021) - Li, Bijun; Guo, Ruixia; Lai, Tianjiao; Qiao, Long; Fu, Hanlin
Abstract: Aim: We aimed to explore the application of PAX1 methylation and human papillomavirus (HPV) E6/E7 mRNA detection in cervical cancer screening and to compare the efficacy with high‐risk (HR)‐HPV detection. Patients and methods: The cervical exfoliative cytology samples of 337 patients were collected, including 70 cases of cervical inflammation, 72 cases of low‐grade squamous intraepithelial lesions, 97 cases of high‐grade squamous intraepithelial lesions, and 98 cases of cervical carcinoma. The PAX1 gene methylation (PAX1) status was detected by multiple quantitative PCR, HPV E6/E7 mRNA (E6/E7) was detected by QuantiVirus detection, and HR‐HPV (HPV) was detected by the Cobas 4800 detection system. The sensitivities, specificities, and accuracies were validated in the testing set. Results: The sensitivities of the HPV, HPV E6/E7, and PAX1 testing were 89.23%, 84.10%, and 86.67%, respectively, which all maintained a high level. In contrast, the specificities of the HPV, E6/E7, and PAX1 testing were only 19.10%, 37.32%, and 97.18% (in pairwise comparisons, p  = 0.000). The AUC of PAX1 (0.919) was significantly larger than that of HPV (0.541) and E6/E7 detection (0.607) ( p  < 0.0001). In addition, the AUC areas of all combined parallel testing were lower than that of single PAX1 test ( p  < 0.05). Conclusion: The diagnostic efficacy of E6/E7 detection and PAX1 detection was better than that of HPV detection, especially for PAX1 detection.